Assessment of students' critical thinking maturity in the process of teaching philosophy - A. I. Pavlovskij; O. V. Pavlovskaya (Russian State Vocational Pedagogical University, 2024)
Introduction. Developing critical thinking is one of the primary objectives of modern education. From the authors' perspective, both the method and the content of the discipline, especially philosophy, have historically evolved through dialogue within the intellectual tradition of the era, which is valuable for fostering critical thinking. Aim. The study aimed to develop and test a methodology for assessing the role of philosophy in shaping critical thinking, considering its expertise, knowledge, and skills. Methodology and research methods. The development of critical thinking was assessed during the analysis of the philosophical text. Prior to the test, it is worth noting that the authors conducted an expert assessment of the text, which later served as a reference assessment, and developed a grading scale. Gradually, examples of typical student errors were added to the scale, facilitating further assessment. Results. Nearly all students were able to summarise the provided text by the end of the course, although with varying degrees of distortion. At the beginning of the course, approximately one-tenth of the students were unable to do it, indicating that the understanding and interpretation of a text was beyond their ability. The absence of dynamics in all three skills indicates that a student has not developed a critical thinking mindset if their results are low. Among the students, the weak and average ones exhibit the most significant overall improvement (16-20% of the class enhance their performance across all criteria). The test revealed tender points in the student's critical thinking development: a feeble argument assessment skill and a poor understanding of the voice behind the text. Scientific novelty. The proposed assessment methodology enables the connection of texts to assess the development of critical thinking with philosophical objectivity. Practical significance. This work provides a convenient tool for monitoring critical thinking skills in each student. Measuring critical thinking skills through students' written works may help track individual accomplishments of the learners and indicate areas of growth in the course taught.